(untitled) (Rudarsko-geološko-naftni zbornik, 2019)
The purpose of this research is to perform an evaluation of the spontaneous combustion of coal (SCC) in Tabas Parvadeh coal mines in Iran, by using the R70 test method based on a the correlation between intrinsic coal properties and the occurrence of its combustion. Firstly, the coal samples were collected from Parvadeh I to IV, and the intrinsic coal properties of the samples were tested. Then, the R70 test method, as the newest method for assessment of the SCC, was used. In the last step, the correlation between intrinsic coal properties and R70 test values was carried out. The results showed that the B1 seam in Parvadeh II and the C1 seam in Parvadeh III have a high propensity of the SCC. The outcomes appear, an expansion of moisture, pyrite,vitrinite,and liptinitecontents enhance the SCC tendency in these mines. The results obtained have major outcomes for the management of this phenomenon in Tabas Parvadeh coal mines.